A method for preparing a polyelectrolyte dip-coated covalent organic framework nanofiltration membrane

CN120733582BActive Publication Date: 2026-10-09TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511187769.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-08-25
Publication Date
2026-10-09
Estimated Expiration
2045-08-25

AI Technical Summary

Technical Problem

但上述策略仍存在显著缺陷,制备工艺复杂导致膜规模化制备困难

Benefits of technology

[0015] This invention employs a simple dip-coating strategy, achieving synergistic control of charge density and pore size in COF membranes by coating the surface of a polyelectrolyte onto the membrane surface. The masking effect of sodium polystyrene sulfonate polymer segments reduces the average pore size of the membrane channels, while sulfonate ions convert the membrane surface from positive to negative charge, thereby significantly enhancing the membrane's retention capacity for a wide range of divalent salts. The materials used in this membrane fabrication process are readily available, the preparation process is simple, the preparation flow is short, and the operation is convenient, making it suitable for large-scale industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120733582B_ABST
    Figure CN120733582B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of a polyelectrolyte dip-coating covalent organic framework nanofiltration membrane, mainly comprising the following steps: preparing TbTG nanosheets, dialyzing a TbTG nanosheet dispersion solution to obtain a TbTG nanosheet aqueous solution, taking a polyethersulfone microfiltration membrane as a base film, vacuum-filtering the base film by using the TbTG nanosheet aqueous solution to obtain an ionic TbTG covalent organic framework membrane, soaking the ionic TbTG covalent organic framework membrane in a sodium polystyrene sulfonate solution, and taking out the ionic TbTG covalent organic framework membrane after standing and reaction, and airing the ionic TbTG covalent organic framework membrane. The application realizes the synergistic regulation of the pore structure and the surface charge density of the COF membrane by combining vacuum-assisted self-assembly and dip-coating, and by dip-coating the polyelectrolyte sodium polystyrene sulfonate on the ionic TbTG covalent organic framework membrane. The ultrathin sodium polystyrene sulfonate layer not only effectively reduces the pore size of the COF membrane and improves the steric hindrance screening effect, but also changes the surface of the membrane from positive to negative, so as to simultaneously improve the rejection rates of the covalent organic framework membrane to magnesium chloride and sodium sulfate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the preparation and application of nanofiltration membranes, and more particularly to a method for preparing polyelectrolyte-coated covalent organic framework nanofiltration membranes. Background Technology

[0002] In modern society, water treatment is a process involving water purification and resource recycling, urgently requiring the development of efficient separation technologies to address multiple objectives. For example, in the chlor-alkali industry, membrane technology is used for the pre-separation of Cl- / SO4. 2- It can significantly reduce energy consumption in subsequent separation processes. In the field of lithium resource extraction, Li + With Mg 2+ The efficient separation of competing cations holds immense economic value. Nanofiltration (NF) membranes, with their advantages of low energy consumption and environmental friendliness, have become a cutting-edge technology for wastewater purification and resource recovery. However, existing nanofiltration membranes primarily carry a single charge (i.e., only positive or negative charges). This characteristic results in excellent retention rates for divalent ions, but limited effectiveness in retaining divalent counterions, restricting their application in various industrial processes. To meet the demands of the new era, developing novel nanofiltration membranes that efficiently retain both divalent cations and anions will greatly expand their applicability.

[0003] Covalent organic frameworks (COFs), as an emerging crystalline material, possess atomically designable physicochemical structures. Their high porosity and customizable channel structures endow them with outstanding membrane separation potential, which has been extensively validated through experimental and simulation studies. However, COF membranes typically struggle to achieve selective ion separation, primarily because their pore size is larger than the hydration diameter of ions. To address this key issue and challenge, current research focuses on two main control strategies: pore confinement enhancement, achieved by constructing bilayer COF membranes with staggered pores, designing inherent sub-nanometer pore structures, or developing hybrid-dimensional membranes to control the pore size; and pore wall functionalization modification, grafting charged groups such as sulfonate or quaternary ammonium groups onto the pore walls of COF membranes to enhance common ion rejection rates by regulating ion-membrane interactions. However, these strategies still have significant drawbacks, with complex fabrication processes hindering large-scale membrane production. Summary of the Invention

[0004] To address the aforementioned limitations of existing technologies, this invention proposes a method for preparing a polyelectrolyte-coated covalent organic framework (COF) nanofiltration membrane. This method involves coating an ionomer COF (TbTG) membrane with a sodium polystyrene sulfonate (PSS) layer, thereby achieving synergistic control over the pore structure and surface charge density of the COF membrane. The ultrathin PSS layer not only effectively reduces the pore size of the COF membrane, enhancing its steric sieving effect, but also transforms the membrane surface from positively charged to negatively charged, aiming to simultaneously improve the retention rates of magnesium chloride and sodium sulfate by the COF membrane.

[0005] To address the aforementioned technical problems, this invention proposes a method for preparing a polyelectrolyte-coated covalent organic framework nanofiltration membrane. This method combines vacuum-assisted self-assembly and dip-coating to coat an ionic TbTG covalent organic framework membrane with the polyelectrolyte sodium polystyrene sulfonate, thereby achieving synergistic control of the pore structure and surface charge density of the ionic TbTG covalent organic framework membrane. The specific steps are as follows:

[0006] Step 1: Preparation of TbTG nanosheets: 1,3,5-trimethylbenzaldehyde was dissolved in an organic solvent at a molar volume ratio of 10 mmol / L to prepare an oil phase solution, and triaminoguanidine hydrochloride was dissolved in an aqueous solvent at a molar volume ratio of 10 mmol / L to prepare an aqueous phase solution. The aqueous phase solution was injected into a container, and then the oil phase solution was slowly added dropwise along the inner wall of the container to the top of the aqueous phase solution using a dropper. The reaction system was then slowly transferred to a biochemical incubator and allowed to stand at room temperature for 2-7 days. TbTG nanosheets were generated in the reaction system.

[0007] Step 2: Purification of TbTG nanosheets: The reaction system is slowly removed from the biochemical incubator, and the upper oil phase solution is aspirated with a dropper, leaving a TbTG nanosheet dispersion in the lower layer; the TbTG nanosheet dispersion is dialyzed with deionized water for 1-7 days to obtain an aqueous solution of TbTG nanosheets, which is then refrigerated and stored for later use.

[0008] Step 3: Synthesizing polyelectrolyte-coated TbTG nanofiltration membranes using a combination of vacuum-assisted self-assembly and dip-coating: A polyethersulfone (PES) membrane was placed on a vacuum filtration apparatus. A certain volume of TbTG nanosheet aqueous solution was placed in a vacuum filtration cup. The apparatus was turned on, and after vacuum filtration, an ionic TbTG covalent organic framework membrane was obtained. After removing obvious droplets from the membrane surface, a certain volume of sodium polystyrene sulfonate solution was slowly added dropwise along the inner wall of the container into the vacuum filtration apparatus using a dropper. After allowing the dip-coating synthesis reaction to proceed, a polyelectrolyte-coated covalent organic framework nanofiltration membrane was obtained, denoted as the TbTG / PSS nanofiltration membrane. The prepared TbTG / PSS membrane was stored in ultrapure water.

[0009] Furthermore, in the preparation method described in this invention, wherein:

[0010] In step one, the organic solvent is a mixed solution of mesitylene and 1,4-dioxane in a volume ratio of 9:1, and the aqueous solvent is a mixed solution of deionized water and acetic acid with a molar concentration of 6 mol / L in a volume ratio of 17:3; in the container, the oil phase solution and the aqueous phase solution are of equal volume; the reaction time is 3-5 days.

[0011] In step two, the dialysis treatment lasts for 2-4 days.

[0012] In step three, the pore size of the polyethersulfone-based membrane is 220 nm; the amount of the TbTG nanosheet aqueous solution used is related to the area of ​​the polyethersulfone-based membrane at a ratio of 130 μL / cm². 2 The sodium polystyrene sulfonate has a molecular weight of 70,000-1,500,000 Da; the sodium polystyrene sulfonate solution has a mass fraction of 0.05-0.50%; the volume ratio of the TbTG nanosheet aqueous solution to the sodium polystyrene sulfonate solution is 1:10-20; and the static dip-coating synthesis reaction time is 5-60 min.

[0013] Preferably, in step three, the mass fraction of the sodium polystyrene sulfonate solution is 0.05-0.20%; and the static dip-coating synthesis reaction time is 20-40 min.

[0014] Compared with the prior art, the beneficial effects of the present invention are:

[0015] This invention employs a simple dip-coating strategy, achieving synergistic control of charge density and pore size in COF membranes by coating the surface of a polyelectrolyte onto the membrane surface. The masking effect of sodium polystyrene sulfonate polymer segments reduces the average pore size of the membrane channels, while sulfonate ions convert the membrane surface from positive to negative charge, thereby significantly enhancing the membrane's retention capacity for a wide range of divalent salts. The materials used in this membrane fabrication process are readily available, the preparation process is simple, the preparation flow is short, and the operation is convenient, making it suitable for large-scale industrial production. Attached Figure Description

[0016] Figure 1 This is a schematic diagram of the preparation process of the polyelectrolyte impregnation-coated covalent organic framework nanofiltration membrane according to the present invention;

[0017] Figure 2(a) and Figure 2(b) are scanning electron microscope images of the surface and cross-section of the TbTG / PSS-4 film prepared in Example 4, respectively.

[0018] Figures 3(a) and 3(b) show the pore size and zeta potential of the TbTG / PSS-4 membrane and TbTG nanofiltration membrane prepared in Example 4 and the comparative example, respectively.

[0019] Figure 4The graph shows the rejection rates of aqueous solutions of magnesium chloride, sodium sulfate, sodium chloride, and lithium chloride (all at a mass fraction of 0.1%) for the TbTG / PSS-4 membrane and TbTG nanofiltration membrane prepared in Example 4 and the comparative example, respectively. Detailed Implementation

[0020] The present invention proposes a method for preparing a polyelectrolyte-coated covalent organic framework nanofiltration membrane. The design concept involves combining vacuum-assisted self-assembly and dip-coating to coat an ionic TbTG covalent organic framework membrane with sodium polystyrene sulfonate, thereby achieving synergistic control of the pore structure and surface charge density of the TbTG covalent organic framework membrane. The ultrathin sodium polystyrene sulfonate layer not only effectively reduces the pore size of the TbTG covalent organic framework membrane, enhancing its steric sieving effect, but also changes the membrane surface from positive to negative charge, aiming to simultaneously improve the retention rate of magnesium chloride and sodium sulfate by the covalent organic framework membrane. Figure 1 As shown, the preparation process mainly includes: preparing TbTG nanosheets, dialyzing the TbTG nanosheet dispersion to obtain an aqueous solution of TbTG nanosheets, using a polyethersulfone microfiltration membrane as the base membrane, vacuum filtering the base membrane with the TbTG nanosheet aqueous solution to obtain an ionic TbTG covalent organic framework membrane (hereinafter referred to as TbTG membrane), immersing the membrane in a sodium polystyrene sulfonate solution for static reaction, removing it, and drying it to finally obtain a polyelectrolyte-coated covalent organic framework nanofiltration membrane (hereinafter referred to as TbTG / PSS membrane).

[0021] The technical solution of the present invention will be further described in detail below with reference to specific embodiments and appendices. The specific embodiments described are only for explanation and illustration of the present invention and are not intended to limit the present invention.

[0022] The separation performance of the TbTG / PSS membrane prepared in this invention is evaluated mainly by two characteristic parameters: the salt rejection rate and the water flux.

[0023] Retention rate calculation formula: R = (1 - C) p / C f )×100%, where R represents the retention rate, C p and C f These are the salt concentrations (ppm) in the permeate and feed solutions, respectively. Unless otherwise specified, the feed solution is a 0.1% (w / w) aqueous solution of magnesium chloride or sodium sulfate.

[0024] Water flux (LMH / bar) is defined as the volume of water passing through the effective membrane area per unit pressure per unit time under certain operating pressure conditions. Unless otherwise specified, the test pressure of the membrane is 4 bar.

[0025] Example 1: Preparation of polyelectrolyte-coated covalent organic framework nanofiltration membrane, the steps are as follows:

[0026] Step 1, Preparation of TbTG Nanosheets: 0.2 mmol of 1,3,5-trimethylbenzaldehyde was dissolved in 20 mL of a 9:1 mixture of trimethylbenzylene and 1,4-dioxane as the oil phase solution. 0.2 mmol of triaminoguanidine hydrochloride was dissolved in 20 mL of a 20 mL mixture of deionized water and acetic acid as the aqueous phase solution. The oil phase solution was slowly added dropwise along the wall of a Shu Niu bottle to the top of the aqueous phase solution using a dropper. The bottle was then slowly transferred to a biochemical incubator and sealed, and the mixture was allowed to react at 25°C for 3 days.

[0027] Step 2, Purification of TbTG Nanosheets: The Shu Niu bottle was slowly removed from the biochemical incubator, and the upper oil phase solution was aspirated with a dropper to obtain the lower TbTG nanosheet dispersion. The dispersion was dialyzed with deionized water for 3 days to remove unreacted monomers and impurities, with the deionized water changed daily during this period. The dialyzed TbTG nanosheet aqueous solution was then stored in a refrigerator for later use.

[0028] Step 3: Reaction synthesis of polyelectrolyte-coated TbTG nanofiltration membrane: The composite nanofiltration membrane is prepared using a combination of vacuum-assisted self-assembly and dip-coating. The specific steps are as follows:

[0029] A 2 cm diameter polyethersulfone (PES) microfiltration membrane was cut and used as the base membrane. The PES membrane was placed on a vacuum filtration apparatus. 400 μL of an aqueous solution of TbTG nanosheets was placed in the filtration cup. The vacuum filtration apparatus was turned on, and vacuum filtration was performed. When no obvious droplets remained on the membrane surface, the filtration apparatus was turned off. This membrane was then the TbTG membrane. 5 mL of a 0.05% sodium polystyrene sulfonate solution (molecular weight 1,000,000) was slowly added dropwise along the bottle wall to the vacuum filtration apparatus. The membrane was allowed to stand for 30 minutes to coat the membrane, resulting in a polyelectrolyte-coated TbTG nanofiltration membrane, denoted as the TbTG / PSS-1 membrane. The prepared TbTG / PSS-1 membrane was stored in ultrapure water for subsequent testing and characterization.

[0030] The TbTG / PSS-1 membrane was tested and found to have a magnesium chloride rejection rate of 96.5% and a sodium sulfate rejection rate of 96.6% (see Table 1). Example 2: Preparation of a polyelectrolyte-coated covalent organic framework nanofiltration membrane. The preparation process was basically the same as in Example 1, except that in step three, the mass fraction of the sodium polystyrene sulfonate solution was changed from 0.05% to 0.10%, ultimately yielding a TbTG / PSS-2 membrane.

[0031] The TbTG / PSS-2 membrane was tested and found to have a magnesium chloride rejection rate of 98.0% and a sodium sulfate rejection rate of 97.7% (see Table 1). Example 3: Preparation of a polyelectrolyte-coated covalent organic framework nanofiltration membrane. The preparation process was basically the same as in Example 1, except that in step three, the mass fraction of the sodium polystyrene sulfonate solution was changed from 0.05% to 0.15%, ultimately yielding a TbTG / PSS-3 membrane.

[0032] Tests showed that the TbTG / PSS-3 membrane had a magnesium chloride rejection rate of 94.2% and a sodium sulfate rejection rate of 97.8%.

[0033] Example 4: Preparation of polyelectrolyte-coated covalent organic framework nanofiltration membrane. The preparation process is basically the same as in Example 1, except that in step three, the mass fraction of the sodium polystyrene sulfonate solution is changed from 0.05% to 0.20%, and a TbTG / PSS-4 membrane is finally obtained.

[0034] Figures 2(a) and 2(b) show scanning electron microscope images of the surface and cross-section of the TbTG / PSS-4 membrane; the magnesium chloride rejection rate of the TbTG / PSS-4 membrane was tested to be 91.7% and the sodium sulfate rejection rate was 98.6% (see Table 1).

[0035] The preparation steps of the comparative covalent organic framework nanofiltration membrane are as follows:

[0036] Step 1: TbTG nanosheets were prepared according to Step 1 of Example 1;

[0037] Step 2: Purify the TbTG nanosheets according to Step 2 of Example 1 to obtain an aqueous solution of TbTG nanosheets;

[0038] Step 3: TbTG film is synthesized using vacuum-assisted self-assembly. The specific steps are as follows:

[0039] A 2 cm diameter polyethersulfone microfiltration membrane was cut and used as the base membrane. The polyethersulfone base membrane was placed on a vacuum filtration device, and 400 μL of an aqueous solution of the TbTG nanosheets prepared in step two was placed in the vacuum filtration cup. The vacuum filtration device was then turned on. When there were no obvious droplets on the membrane surface, the vacuum filtration device was turned off to obtain the TbTG nanofiltration membrane.

[0040] The TbTG nanofiltration membrane prepared in the comparative experiment showed a magnesium chloride rejection rate of 88.3% and a sodium sulfate rejection rate of 70.3% (see Table 1).

[0041] Figures 3(a) and 3(b) show the changes in pore size and Zeta potential of the TbTG / PSS-4 and TbTG nanofiltration membranes prepared in Example 4 and the comparative example, respectively, as a function of pH. It can be seen that the TbTG / PSS-4 membrane of the present invention has a smaller pore size than the TbTG nanofiltration membrane of the comparative example. When the pH value changes between 3 and 10, the Zeta potential of the TbTG / PSS-4 membrane is always lower than that of the TbTG nanofiltration membrane and is negative. This indicates that the TbTG / PSS-4 membrane has stronger negative charge characteristics than the TbTG nanofiltration membrane.

[0042] Figure 4 The graph shows the rejection rates of the TbTG / PSS-4 membrane prepared in Example 4 for aqueous solutions of magnesium chloride, sodium sulfate, sodium chloride, and lithium chloride (all with a mass fraction of 0.1%). It can be seen that the rejection rates of the TbTG / PSS-4 membrane for salts containing divalent cations (magnesium chloride and sodium sulfate) are all higher than 98.0%.

[0043] Table 1 shows a comparison of the magnesium chloride and sodium sulfate rejection rates of the membranes prepared in the various embodiments of the present invention and the comparative membranes prepared in the comparative examples:

[0044] Table 1 Test data of embodiments and comparative examples of the present invention

[0045]

[0046] Based on the preparation conditions of all the above embodiments and comparative examples, and Table 1 and... Figure 1-4 It can be concluded that as the concentration of sodium polystyrene sulfonate solution increases, the rejection rates of magnesium chloride and sodium sulfate by the nanofiltration membrane first increase and then decrease. Specifically, based on the results of the comparative example and Example 4, sodium polystyrene sulfonate can increase the surface charge density of the nanofiltration membrane and reduce the average pore size of the membrane.

[0047] In summary, the materials used in this invention are readily available, the preparation process is simple, the process is short, and the operation is convenient. TbTG nanosheets are self-assembled on the surface of a polyethersulfone-based membrane using vacuum assistance, and then a polyelectrolyte-coated covalent organic framework nanofiltration membrane is prepared by surface coating with sodium polystyrene sulfonate. Because the sulfonate ions of sodium polystyrene sulfonate are introduced into the membrane surface, the negative charge density of the membrane is enhanced. At the same time, the shielding effect of sodium polystyrene sulfonate reduces the pore size of the covalent organic framework membrane, thereby simultaneously improving the membrane's rejection rate for magnesium ions and sulfate ions.

[0048] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many changes under the guidance of the present invention without departing from the spirit of the present invention, and these changes are all within the protection scope of the present invention.

Claims

1. A method for preparing a polyelectrolyte-coated covalent organic framework nanofiltration membrane, characterized in that, A combination of vacuum-assisted self-assembly and dip-coating was used to dip-coat a polyelectrolyte sodium polystyrene sulfonate onto an ionic TbTG covalent organic framework membrane, achieving synergistic control of the pore structure and surface charge density of the membrane. The sulfonate groups of sodium polystyrene sulfonate were introduced into the membrane surface. This preparation method includes the following steps: Step 1: Preparation of TbTG nanosheets; Step 2: Purification of TbTG nanosheets; Step 3: Synthesize polyelectrolyte-coated TbTG nanofiltration membrane using a combination of vacuum-assisted self-assembly and dip-coating: Place the polyethersulfone-based membrane on a vacuum filtration device, take a certain volume of TbTG nanosheet aqueous solution in the vacuum filtration cup, turn on the vacuum filtration device, and obtain an ionic TbTG covalent organic framework membrane after vacuum filtration. After removing obvious droplets from the membrane surface, slowly add a certain volume of sodium polystyrene sulfonate solution along the inner wall of the container to the vacuum filtration device using a dropper. After allowing the dip-coating synthesis reaction to stand, a polyelectrolyte-coated covalent organic framework nanofiltration membrane is obtained, denoted as TbTG / PSS nanofiltration membrane.

2. The preparation method according to claim 1, characterized in that, The process of preparing TbTG nanosheets in step one is as follows: 1,3,5-trimethylbenzaldehyde is dissolved in an organic solvent at a molar volume ratio of 10 mmol / L to prepare an oil phase solution, and triaminoguanidine hydrochloride is dissolved in an aqueous solvent at a molar volume ratio of 10 mmol / L to prepare an aqueous phase solution. The aqueous phase solution is injected into a container, and then the oil phase solution is slowly added dropwise along the inner wall of the container to the top of the aqueous phase solution using a dropper. The reaction system is then slowly transferred to a biochemical incubator and sealed and allowed to stand at room temperature for 2-7 days. TbTG nanosheets are generated in the reaction system. The purification process of TbTG nanosheets in step two is as follows: the reaction system is slowly removed from the biochemical incubator, the upper oil phase solution is aspirated with a dropper, and the lower layer is a TbTG nanosheet dispersion; the TbTG nanosheet dispersion is dialyzed with deionized water for 1-7 days to obtain an aqueous solution of TbTG nanosheets, which is then refrigerated and stored for later use.

3. The preparation method according to claim 2, characterized in that, In step one, the organic solvent is a mixed solution of mesitylene and 1,4-dioxane in a volume ratio of 9:1, and the aqueous solvent is a mixed solution of deionized water and acetic acid with a molar concentration of 6 mol / L in a volume ratio of 17:3; in the container, the oil phase solution and the aqueous phase solution are of equal volume; the reaction time is 3-5 days.

4. The preparation method according to claim 2, characterized in that, In step two, the dialysis treatment lasts for 2-4 days.

5. The preparation method according to claim 2, characterized in that, In step three, the pore size of the polyethersulfone-based membrane is 220 nm; the amount of the TbTG nanosheet aqueous solution used is related to the area of ​​the polyethersulfone-based membrane at a ratio of 130 μL / cm². 2 The sodium polystyrene sulfonate has a molecular weight of 70,000-1,500,000 Da; the sodium polystyrene sulfonate solution has a mass fraction of 0.05-0.50%; the volume ratio of the TbTG nanosheet aqueous solution to the sodium polystyrene sulfonate solution is 1:10-20; and the static dip-coating synthesis reaction time is 5-60 min.

6. The preparation method according to claim 5, characterized in that, The sodium polystyrene sulfonate solution has a mass fraction of 0.05-0.20%.

7. The preparation method according to claim 5, characterized in that, The static dip-coating synthesis reaction time is 20-40 min.